The Art Of Explaining Complex Financial Reports To Non-Experts Using Simplified English - Uktam kizi, Xasanova Sitora; Abdiyeva Oysha Ro‘zimurod kizi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This article explores effective methods for explaining complex financial reports to non-experts using simplified English. Financial documents such as balance sheets, income statements, and cash flow reports often contain technical terminology and detailed data that can be difficult for ordinary readers to understand. The study emphasizes the importance of using plain language, clear structure, and real-life examples to improve comprehension. The article concludes that simplifying financial language enhances financial literacy and supports better decision-making among non-specialists.